The Development of Questions in Child and Child-directed Speech in Turkish - Vildan İnci KAVAK (Dilbilim Araştırmaları Dergisi)
Child-directed questions are significant in high-quality mother-child interactions (Ninio, 1980; Rowe, Leech & Cabrera., 2017). This paper examines the probable effects of Turkish child-directed speech (CDS) on the acquisition of wh-words of a Turkish child. In this study, the spontaneous speech of a Turkish boy and his mother was video recorded weekly between the ages of 20 and 22 months by his mother during day-time activities such as play, meals and leisure time. Then, it was studied to identify the frequency and the form as directed to the child. The results were compared to understand how the frequency and form of questions changed over three months. While yes/no questions and wh-pronominals with the copula and with semantically general verbs were the question forms found substantially in child-directed speech, the child only produced intonation questions. It was revealed that there is a close relationship between input and acquisition at the sentence and verb level in the present data. This study contributes to language acquisition studies by enhancing our knowledge of how Turkish children acquire questions.